Emotional states of athletes prior to performance-induced injury - Devonport, T. J.; Lane, A. M.; Hanin, Y. L. (Journal of Sports Science & Medicine, 2005)
Psychological states experienced by athletes prior to injured, best and worst performances were investigated retrospectively using a mixed methodology. Fifty-nine athletes volunteered to complete an individualized assessment of performance states based on the Individual Zones of Optimal fFunctioning (IZOF) model. A subsection (n = 30) of participants completed a standardized psychometric scale (Brunel Mood Rating Scale: BRUMS), retrospectively describing how they felt before best, worst, and injured performances. IZOF results showed similar emotion states being identified for injured and best performances. Analysis of BRUMS scores indicated a significant main effect for differences in mood by performance outcome, with post-hoc analyses showing best performance was associated with lower scores on depression and fatigue and higher vigor than injured performance and worst performance. Worst performance was associated with higher fatigue and confusion than injured performance. Results indicate that retrospective emotional profiles before injured performance are closer to successful performance, than unsuccessful, and confirm differences between successful and unsuccessful performance. Qualitative and quantitative approaches used to retrospectively assess pre-performance emotional states before three performance outcomes, produced complimentary findings. Practical implications of the study are discussed.